Un jeu sérieux dans un cours universitaire de FLE : analyse de l’implication des étudiants - Dora Loizidou; François Mangenot (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This article analyses the integration of a serious game into a blended university course in French as a foreign language. This game, Enterre-moi mon amour, is an interactive fiction situated in the context of the war in Syria and the refugee crises it provoked. It provides players with an interactive and immersive experience in which their choices significantly impact the story’s unfolding. Students play an active role in the protagonist’s story and must make choices at various points. Each choice leads to a different situation, so the reader is responsible for the course and outcome of the story. Immersion in emotional situations, whether real or fictional, promotes language learning. Therefore, we examine in this research how and to what extent students become involved in the game. We conducted a content analysis of the students’ written productions to test the hypothesis of a solid but diverse involvement on the part of most of our students.